Instrument-based detection methods for adulteration in spice and spice products – A review - C Anandharamakrishnan, S K V Bharathi, A Sukitha, J A Moses, (Journal of Spices and Aromatic Crops, 2019)
Spices play an important role as flavorants, colorants, preservatives and bioactive compounds in medical, food and cosmetic applications. India is the spice bowl of the world and spice production is scattered across the country. Almost every stage of production, including cultivation, harvest, handling, storage, transportation and distribution has impact on spice quality. Adulterants are often intentionally added to fetch better market value through inferior/ unacceptable quality products. Adulterants are a concern to quality, market compliancy and food safety. Over the years, several approaches for quantitative and qualitative detection of adulterants have been developed. Though basic and simple testing methods are available to detect the presence of adulterants, instrument based techniques are often adapted to detect the adulterants quantitatively. The objective of this work is to present a detailed note on these approaches with emphasis on the various analytical techniques used in the detection and quantification of adulterants in spice and spice products.